Tecnologias Digitais da Informação e Comunicação e aprendizagem curricular em museus: um estudo na cidade de São Paulo - Sampaio, Romilson Lopes (2014)
The steady advance of Digital Technologies of the Information and Communication (TDIC) creates new institutional ways to educational processes, and the museum, situated in this context it presents itself as an Institution of non-formal education, whose educational potential allied to TDIC, can transform the learning in a meaningful, effective and enjoyable process. This research aims to verify as TDIC has utilized to explore this educational potential that São Paulo City has in some museological space. Then, it has realized a fieldwork having as a locus of investigation the museums have TDIC in their shows and attend to infant public from public school of that city. The informants of the research were students of in the end basic education (6º to 9º level), the teachers that follow during the visits, the responsible professionals for educational sector and mediators of those Institutions. It had used, as instruments of data collections, the observation and interviews. The observation has done, from guided visits to two museums of São Paulo City and the interviews had realized with responsible professionals by educational sector and by two mediators of the same surveyed. The process of analysis has guided for theoretical lectures that allow significant stretches and the preparation of a category of analysis. The listed data had analyzed to capture, naturally, the behavior of the students, teachers and mediators, during the visits of the school groups to these institutions, beyond of your interactions with TDIC, available in these locals. Moreover, this approach can analyze the opinions of professionals of the museums about the use of these technologies during the visits. The results indicate these spaces have a big educational potentials and TDIC uses are essential to the same can follow of the demands by present, allowing to be closer of young public that visit them. The use of these technologies can help the work in these museological Institutions too, as potentiating the learning of a specific subject in relation to students, as allowing a large approach those visitors with the show. However, it is noteworthy that technology doesn t bring solutions alone for the problems, either school or museums and its use will only bring the expected benefits if it had previous been done studies of preparation, implementation and use. Then, the technology mustn t be more important than museum, and its use can t replace the exposed object, but it contributes to your better understanding